Women of the Nottinghamshire elite, c. 1720-1820 - Dunster, Sandra (2003)
This thesis explores the lives of women in a small group of families in the Nottinghamshire elite between 1720 and 1820. A close reading of family papers, gives access to the minutiae of female life and it is from these small details that the attitudes, activities and responsibilities of elite women are constructed. Drawing on the distinct historiographies of women and gender, and of the elite, the evidence produced by this sharply-focused approach is used to explore women's formal and informal roles, and the specific ways in which they were fulfilled, in the domestic, social, economic and political life of the elite.